THE LEGAL POLICY ON THE ESTABLISHMENT OF AD HOC AGRARIAN COURTS AS AN INSTRUMENT FOR RESOLVING AGRARIAN CONFLICTS IN INDONESIA - Hermawan; Andi Muhammad Rusdi (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
Agrarian disputes in Indonesia persist as a multifaceted and persistent challenge, entangling stakeholders including communities, authorities, and businesses. Existing mechanisms for resolving such conflicts remain disjointed, dispersed across forums like general courts and state administrative tribunals, frequently yielding juridical ambiguity and suboptimal outcomes. This inquiry evaluates the necessity and optimal juridical architecture for instituting an ad hoc agrarian tribunal as a pathway to holistic conflict adjudication. Employing normative legal methodology with statutory and conceptual emphases, it draws upon pertinent legislation, monographs, and scholarly publications. Findings affirm the imperative for an ad hoc agrarian court to rectify systemic fragmentation in dispute resolution, delivering equitable verdicts via specialized ad hoc judges expert in agrarian matters. Optimally, this tribunal should function as a specialized entity subordinate to the Supreme Court, wielding unified jurisdiction over agrarian contentions and bolstered by alternative resolution tools like mediation. Accordingly, such a court promises to enhance juridical predictability, uphold communal entitlements, and advance agrarian reform toward equitable social outcomes in land affairs.